The Power of Verbal Expression Examining Language Function in the Short Film ‘The Darkest Blue' - Kamalina, Laela; Ilmiyah, Fasikhatul; Aulia , Sandina Tasya (Department of Master of Linguistic, Universitas Airlangga, 2023)
This research aims to examine and describe the language functions employed in the dialogues by the cast of the short film